Intravital and Whole-Organ Imaging Reveals Capture of Melanoma-Derived Antigen by Lymph Node Subcapsular Macrophages Leading to Widespread Deposition on Follicular Dendritic Cells - Moalli, Federica; Proulx, Steven T.; Schwendener, Reto; Detmar, Michael; Schlapbach, Christoph; Stein, Jens V. (Frontiers in Immunology, 2015)
Aberrant antigens expressed by tumor cells, such as in melanoma, are often associated with humoral immune responses, which may in turn influence tumor progression. Despite recent data showing the central role of adaptive immune responses on cancer spread or control, it remains poorly understood where and how tumor-derived antigen (TDA) induces a humoral immune response in tumor bearing hosts. Based on our observation of TDA accumulation in B cell areas of lymph nodes (LNs) from melanoma patients, we developed a premetastatic B16.F10 melanoma model expressing a fluorescent fusion protein, tandem dimer Tomato, as a surrogate TDA. Using intravital two-photon microscopy (2PM) and whole mount 3D LN imaging of tumor-draining LNs in immunocompetent mice, we report an unexpectedly widespread accumulation of TDA on follicular dendritic cells (FDCs), which were dynamically scanned by circulating B cells. Furthermore, 2PM imaging identified macrophages located in the subcapsular sinus of tumor-draining LNs to capture subcellular TDA-containing particles arriving in afferent lymph. As a consequence, depletion of macrophages or genetic ablation of B cells and FDCs resulted in dramatically reduced TDA capture in tumor-draining LNs. In sum, we identified a major pathway for the induction of humoral responses in a melanoma model, which may be exploitable to manipulate anti-TDA antibody production during cancer immunotherapy.